Paleoenvironmental variations during the Late Cambrian: Implications from Zn isotopes, I/(Ca+Mg) ratios, and other elemental proxies - González Robacio, Luisa; Azmy, Karem; Guéguen, Bleuenn; Claret, Francis (Marine and Petroleum Geology, 2024)
International audience The Upper Cambrian at the Martin Point section (∼110 m-thick) in western Newfoundland is a part of the Cow Head Group and partially spans the coeval Tuckers Cove and the Martin Point members of the Shallow Bay and Green Point formations, respectively. These units comprise alternating shale, minor conglomerate beds, and limestone rhythmites of a toe-of-slope apron. Earlier studies of the C-isotope profile, based on the lime mudstone interbeds, documented global negative δ13Ccarb shifts (from old to young: NL1, NL2, HERB) correlated with the lowermost Proconodontus posterocostatus, Proconodontus muelleri and base of Eoconodontus notchpeakensis conodont zones, respectively (post-Steptoean Positive Carbon Isotope Excursion NL1 and NL2 and Hellnmaria-Red Tops Boundary-HERB). Samples were extracted from the most preserved spots of micritic to near-micritic grain size (≤4 μm−10 μm). Fabric retention confirms petrographic preservation and insignificant correlations (R2 ≤ 0.1) of diagenetic proxies (e.g., Sr) with their environmental counterparts support the preservation of at least near-primary geochemical signatures. The paleoenvironmental proxies (TOC, Zn, P, Cu, Al/Ti, Mn, Fe, V, Mo) support dominant dysoxic conditions. The δ66Zn values (0.09–0.73 ‰ JMC Lyon) and (I/(Ca + Mg)) ratios (0.02–0.48 μmol/mol) vary consistently throughout the studied events. The minor decreases in δ66Zn values seem to denote inhibition of bioproductivity in a dysoxic water column, consistent with warm and humid climate during general transgressive settings and shoaling of organic-rich water into the shallow environment. The low I/(Ca + Mg) ratios (<0.5 μmol/mol) reinforce this interpretation, suggesting general dysoxic settings throughout the entire section.